2017
DOI: 10.1063/1.5000530
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature on Rb and 129Xe spin polarization in a nuclear magnetic resonance gyroscope with low pump power

Abstract: We propose an average Rb polarization model to analyze the influence of temperature on the spin polarization of Rb and 129Xe in a Nuclear Magnetic Resonance Gyroscope (NMRG) with low pump power. This model is essentially based on summing the Rb spin polarization along the direction of the pump beam and dividing the result by the cell length. We experimentally study the spin polarization of Rb and 129Xe atoms as a function of the cell temperature at low values of the pump power. The experimental results and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 19 publications
1
7
0
1
Order By: Relevance
“…In conclusion, the coupled spin polarization modelling process for Rb and Xe atoms ensemble of a nuclear magnetic resonance gyroscope is presented in detail. Based on the model, the three dimensional distribution of the spin polarization field of Rb and Xe atoms is obtained by numerical solution and the results are in good agreement with the experiment results obtained by L. Chen et al [5]. Influencing factors including temperature, power and detuned frequency of the pumping laser, anti-relaxation coatings and partial pressure of gas composition are investigated.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…In conclusion, the coupled spin polarization modelling process for Rb and Xe atoms ensemble of a nuclear magnetic resonance gyroscope is presented in detail. Based on the model, the three dimensional distribution of the spin polarization field of Rb and Xe atoms is obtained by numerical solution and the results are in good agreement with the experiment results obtained by L. Chen et al [5]. Influencing factors including temperature, power and detuned frequency of the pumping laser, anti-relaxation coatings and partial pressure of gas composition are investigated.…”
Section: Discussionsupporting
confidence: 72%
“…2 shows the 87 Rb electron spin polarization averaged over the cell varying with the cell temperature through simulation. In order to verify the polarization model and the numerical solution, reference is made to the experiment data of L. Chen et al 5 . These data are from the Fig.…”
Section: Influence Of Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22] However, when there are noble gas atoms which require to be hyper-polarized, many research indicated that 1 mW pump power is generally not sufficient. [23][24][25][26] This causes great challenges to the development of compact atomic gyroscopes.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of quantum technology, specific magnetic field coils are increasingly required in many applications, [1] such as atomic clock, [2,3] optical pumped magnetometer, [4][5][6][7][8] nuclear magnetic resonance gyro, [9,10] and magnetic trap. [11][12][13][14][15] Although many kinds of magnetic coils [14][15][16][17][18][19][20][21][22][23] have been invented for these applications respectively, there is still a lack of a common method to design these coils conveniently, or even to realize any required magnetic field systematically.…”
Section: Introductionmentioning
confidence: 99%